Ring droplet formation during evaporation of a sessile water droplet on a biphilic surface. (January 2022) - Cheng, Hui-Chung; Li, Cheng-Han; Chang, Tien-Li; Chen, Ping-Hei
Highlights: Biphilic surfaces with ring patterns were prepared using the sol-gel method and a picosecond laser. Bubble dynamics during droplet evaporation were analyzed using a high-speed camera. Formation of a ring-shaped droplet with increased heat transfer was observed. The experimental data were compared with a theoretical model. Abstract: Numerous studies have investigated droplet evaporation on surfaces with different roughness and wettability values. However, most studies have focused on droplet evaporation from homogeneous surfaces at low surface temperatures (below 100 °C). In this study, we conducted droplet evaporation experiments on biphilic surfaces with different ring pattern sizes fabricated by a hybrid method consisting of the sol-gel approach and a picosecond laser system. This study investigated the droplet evaporation boiling phenomenon on these biphilic surfaces under superheated conditions. Changes in droplet geometry and inner bubble dynamics during evaporation were analyzed using a high-speed camera. A ring-shaped droplet formed during the final evaporation period. The formation of the ring enhanced the droplet evaporation efficiency. Furthermore, the experimental results from this study work were compared with the theoretical model proposed in the literature. Graphical abstract: Image, graphical abstract